PENGARUH KEPEMIMPINAN DAN KEDISIPLINAN TERHADAP PRODUKTIFITAS KERJA KARYAWAN PADA PT.YAMAHA SERBAMULIA AUTO CABANG LAMBUNG MANGKURAT - Mardiana, Henie Dwi Hastuti, H. Eddy Soegiarto K (EKONOMIA, 2016)
Human Resources need to be managed and developed continuously in order to obtain qualified human resources in the true sense, the implementation of the work will produce something that is desired. Leadership and discipline are interrelated, because with good leadership then a employees will be working more disciplined in working objective of this study to determine the effect of leadership and discipline in improving the productivity of employees at Noble Auto Branch Multipurpose PT.Yamaha Mangkurat Samarinda. This thesis research results show that the variable leadership (X1) and variable Discipline (X2) positive and significant impact on employee productivity variable PT.Yamaha Serba Mulia Auto (Y). With thitungÂ  amounted to 3.639> t table 1.686 and significance 0.001 <0.05. Discipline (X2) in this study has a positive and significant impact on employee productivity (Y) partially because thitungÂ  which 2,938> t table 1.686 and significance 0.006 <0.05.